Bolivia : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that Bolivia's overall fiscal position has improved in 2008. Booming hydrocarbon and mining exports, together with high remittance inflows, led to a record-high current account surplus and large reserve accumulation, with major pressures on monetary/exchange rate policy during the first three quarters of 2008. Executive Directors have noted that strong hydrocarbon and mining exports have continued to support Bolivia's growth and macroeconomic performance. Directors have also emphasized the importance of well-designed structural reforms for further strengthening Bolivia's fiscal position.